Adaptasi Tokoh Makima Dalam Anime Chainsaw Man Pada Make Up Karakter: Make up Makima's character for the occasion of the evening party - Mila Karmila; Arisanty, Regita (Universitas Negeri Jakarta, 2024)
Anime is a typical Japanese animation, usually characterized by colorful images featuring characters in diverse locations and stories, aimed at various types of audiences. One of the famous anime in Japan is Chainsaw Man. Makima is one of the most beautiful and strongest characters from the Chainsaw Man animation, whose appearance is ordinary, has long pink hair tied back, and also has a characteristic orange eyeball. Behind her beautiful and calm face, Makima is known as a very cunning and manipulative figure in the Chainsaw Man animation. Character makeup is applied to change a person's appearance in terms of age, character, face, tribe, and nation to suit the character being played. The purpose of this research is to apply the basics of makeup to create character makeup by adapting the character Makima, thereby developing the knowledge and skills obtained during college, particularly in the concentration of makeup.